Severe trauma in Germany and Israel: are we speaking the same language? A trauma registry comparison - Kaim, Arielle; Bodas, Moran; Bieler, Dan; Radomislensky, Irina; Matthes, Gerrit; Givon, Adi; Trentzsch, Heiko; , Israel Trauma Group; Waydhas, Christian; Lefering, Rolf (Frontiers in Public Health, 2023)
Background: Trauma registries are a crucial component of trauma systems, as they could be utilized to perform a benchmarking of quality of care and enable research in a critical but important area of health care. The aim of this study is to compare the performance of two national trauma systems: Germany (TraumaRegister DGU®,TR-DGU) and Israel (Israeli National Trauma Registry,INTR) in a retrospective analysis. Methods: The present study was a retrospective analysis of data from the described above trauma registries in Israel and Germany. Adult patients from both registries treated during 2015-2019 with an Injury Severity Score (ISS) ≥ 16 points were included. Patient demographics, type, distribution, mechanism, and severity of injury, treatment delivered and length of stay (LOS) in the ICU and in the hospital were included in the analysis. Results: Data were available from 12,585 Israeli patients and 55,660 German patients. Age and sex distribution were comparable, and road traffic collisions were the most prevalent cause of injuries. The ISS of German patients was higher (ISS 24 versus 20), more patients were treated on an intensive care unit (92% versus 32%), and mortality was higher(19.4% versus 9.5%) as well. Conclusion: Despite similar inclusion criteria (ISS ≥ 16) remarkable differences between the two national datasets were observed. Most probably this was caused by different recruitment strategies of both registries, like trauma team activation and need for intensive care in TR-DGU. More detailed analyses are needed to uncover similarities and differences of both trauma systems.